A New Initiative With Multiple Sponsors to Help Prepare Medical Students to Be Safe and Effective Prescribers. Issue 3 (18th February 2015) - Nierenberg, D; Cannon, E
Abstract : Most medical schools in the US, and in other countries as well, continue to struggle to teach their medical students to be safe and effective prescribers before they graduate and set off for their residency programs. We describe a new initiative supported by several national organizations to help medical schools address this need by producing and making available online learning modules that can be used by medical students at any US medical school.